Bimbingan Perkembangan: Model Bimbingan dan Konseling di Sekolah Dasar - Ahman Ahman (Universitas Negeri Malang, 2016)
The purpose of this research is to find out a model of developmental guidance and counseling (GC) in elementary schools. This study was conducted in four stages: development of a hypothetical model, judgment of the model, try out of the model, and development of the recommended model. As a result, the model of developmental GC consists of vision and mission, developmental tasks and needs of elementary school students, purposes of GC services, scope of guidance activities, and system support. Implementation of GC programs is integrated in all educational activities especially in teaching learning process. The Developmental GC Model is effective to improve the developmental tasks and achievement of students